HSP105 expression in oral squamous cell carcinoma: Correlation with clinicopathological features and outcomes. (21st March 2020) - Arvanitidou, Souzana; Martinelli‐Kläy, Carla P.; Samson, Jacky; Lobrinus, Johannes A.; Dulguerov, Nicolas; Lombardi, Tommaso
Abstract: Background: Heat shock proteins (HSPs) are released in response to stress situations, such as heat, inflammation, and infection. They are also involved in the tumor cell proliferation and prevention of apoptosis. Heat shock protein 105 (Hsp105/110) is a high‐molecular‐weight protein, which has been reported in many cancer types but few studies have been carried out on oral squamous cell carcinoma (OSCC). In the current study, we have focused on HSP105 expression on OSCC and evaluated their correlation with tumor clinicopathological parameters and patients' survival. Methods: A retrospective study included 70 patients with OSCC of which 50 patients (71.4%) were male and 20 (28.6%) were female. The patient's information, including age, location, TNM stage, histological grade, regional metastasis, recurrence, and survival, were collected. Immunohistochemical staining for HSP105 was performed. The healthy oral mucosa (n = 10) was used as a control. The staining intensity and percentage of stained cells were semi‐quantitatively evaluated, and HSP105 expression was correlated with tumor clinicopathological features and patient survival. Results: Statistical analysis for HSP105 showed that there was no significant correlation with tumor clinicopathological features. However, HSP105 overexpression was associated with a decrease in the duration of patients' survival ( P  = .042). Conclusion: This result suggests that the increased expression of the HSP105 in the OSCC could be a prognostic factor for malignancy.